The Impact of Age on Outcomes in Seizure Hospitalizations—Analysis of a National Sample - Anudeep Surendranath; Saurabh Singhal; Rahul Khanna; Subhendu Rath; Temenuzhka Mihaylova (Neurology International)
Objective: Seizures are a critical public health issue, with incidence rising significantly after age 50. Using this inflection point, we divided patients into two age groups to examine the impact of age on patient characteristics and hospitalization outcomes for seizures. Methods: Using the 2021 National Inpatient Sample (NIS), a nationally representative database, we conducted a retrospective cohort analysis of adult patients aged ≥18 years admitted with a principal diagnosis of seizures. Patients were divided into two age groups: 18–49 and ≥50 years. Outcomes included in-hospital mortality, length of stay, and hospital charges. Multivariate logistic and linear regression models adjusted for confounders were employed to assess the association between age and outcomes. Results: The cohort included 211,055 patients, with 59% aged ≥50 years. Older patients were more likely to have Medicare coverage (66% vs. 16%, p < 0.01), to reside in the south (41% vs. 38%, p < 0.01), and to have a higher proportion of White individuals (62% vs. 54%, p < 0.01). Younger patients were more likely to be Hispanic (15% vs. 9%, p < 0.01), admitted to urban hospitals (96% vs. 94%, p < 0.01), and treated at teaching hospitals (84% vs. 79%, p < 0.01). After adjusting for confounders, older adults had over twice the odds of in-hospital mortality compared with younger patients (adjusted OR 2.17; 95% CI, 1.61–2.92; p < 0.01). They also experienced longer hospital stays (mean difference 0.7 days; 95% CI, 0.54–0.92; p < 0.01) and higher hospital charges (mean increase USD 4322; 95% CI, USD 1914–6731; p < 0.01). Significance: Age is an independent predictor of in-hospital mortality, longer hospitalizations, and higher costs in seizure-related admissions. These findings underscore the need for age-specific management strategies to improve outcomes and optimize healthcare resource utilization for older adults with seizures.